Peran Struktur Modal sebagai Variabel Mediasi pada Pengaruh Corporate Governance dan Karakteristik CEO terhadap Kinerja Perusahaan - hersugondo hersugondo; Aditya Aliyuna (AFRE (Accounting and Financial Review), 2024)
This study aims to determine the direct effect between corporate governance (CG) and CEO characteristics on firm performance or through capital structure as a mediating variable. This research uses secondary data which consists of a population listed companies Indonesian Stock Exchange from 2017-2022. Purposive sampling method is used in this research, obtaining 241 data. The data were analyzed using Structural Equation Modeling (SEM). The results show that CG has a positive effect on firm performance, while CEO characteristics have no direct effect on firm performance. CG has a positive impact on capital structure as measured by debt to assets ratio (DAR) and debt to equity ratio (DER), while CEO characteristics such as age and tenure have a negative impact on capital structure. Capital structure has a negative impact on firm performance. Capital structure is also able to mediate the impact of CG on firm performance, although it is an inconsistent form of partial mediation. Capital structure has been shown to fully mediate the effect of CEO characteristics on firm performance.DOI: https://doi.org/10.26905/afr.v7i1.12422